Engineering as an instrumentation for improving building efficiency - Shevchuk, K. I. (Ways to Improve Construction Efficiency, 2020)
The article explores the historical aspects of development, the nature and types of engineering, analyzes the stages and formation of engineering in the construction of Ukraine. It is revealed that the engineering services market in Ukraine is at the stage of formation, which is explained by insufficient demand for complex engineering services, the presence of errors in the projects due to lack of sufficient experience, lack of qualified personnel, poor quality of work, outdated normative base, corruption phenomena at the stage of approval and examination of documentation, low level of automation of project work, etc. A historical analysis of the formation of engineering activities in the world. Three stages of engineering development, legislative and legal preconditions and their influence on the development of this concept have been identified. The review and comparison of approaches to engineering activities, including such as: consultative, works and services, creative application of scientific methods and principles, «TRVZ – engineering», organizational engineering in management, engineering of business processes, engineering as a process of health improvement, enterprises, firms, of companies by taking technical solutions to a new level that were not previously reviewed, theoretical approaches and classifications of types of engineering were reviewed, among which consulting, design, research, and scientific were highlighted - capacious, organizational, business process engineering, cost, technological, revitalization, etc. It is determined that in Ukraine the appropriate legal field is created for further development of engineering in construction as a tool that will provide prompt, adequate, timely response to changes in the economic environment and ensure efficiency improvement It is determined that the level of training of specialists is important for the cost estimation of engineering decisions. The list of competencies required for a specialist in cost engineering is offered.